2012
DOI: 10.1007/s00774-012-0408-7
|View full text |Cite
|
Sign up to set email alerts
|

Familial resemblance of bone turnover rate in men aged 40 and over—the MINOS study

Abstract: Familial resemblance of bone mineral density (BMD) is well known in both sexes. Fewer data concern the familial resemblance of bone turnover markers (BTMs) and bone size in men. Our aim was to assess the correlation of BMD, bone size, BTM levels and hormones regulating bone turnover in 50 pairs of brothers aged ≥ 40 and 50 pairs of unrelated men matched for age, weight and height. BMD was measured at the lumbar spine, hip, forearm and whole body. We measured serum osteocalcin (OC), bone-specific alkaline phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Although the present study was not designed to discriminate whether this familial resemblance is due to genetic or environmental factors, evidence from twin studies suggested an important genetic component . Moreover, between‐brother correlations of bone turnover markers in older men were comparable to those in our population, suggesting that the familial resemblance of bone turnover cannot be entirely accounted for by shared environmental factors …”
Section: Discussionmentioning
confidence: 53%
“…Although the present study was not designed to discriminate whether this familial resemblance is due to genetic or environmental factors, evidence from twin studies suggested an important genetic component . Moreover, between‐brother correlations of bone turnover markers in older men were comparable to those in our population, suggesting that the familial resemblance of bone turnover cannot be entirely accounted for by shared environmental factors …”
Section: Discussionmentioning
confidence: 53%
“…These data confirm the role of heritability in the variation of bone turnover in men. In 50 pairs of brothers aged ≥40 years (not twins), BTM (OC, PINP, DPD, CTX-I) correlated positively, and their correlations were significant after adjustment for confounders [25].…”
Section: Discussionmentioning
confidence: 99%